information! the ultimate employer/l'information! de A a Z : PROCEEDINGS OF THE TENTH ANNUAL CANADIAN CONFERENCE ON INFORMATION SCIENCE/COMPTES RENDUS DE LA DIXIEME CONFERENCE ANNUELLE CANADIENNE DES SCIENCES DE L'INFORMATION - Canadian Association for Information Science (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF